2015
DOI: 10.1007/s13187-015-0911-3
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Community Education in Increasing Knowledge of Breast Health and Cancer: Findings from the Asian Breast Cancer Project in Boston, Massachusetts

Abstract: In the past decade, cancer rates have significantly decreased in the USA, but breast cancer survival is lower in Asian American women, likely due to lower rates of screening behaviors in Asian Americans compared to other ethnicities, which could lead to later stage cancer diagnosis and increased mortality. This paper reports on the Asian Breast Cancer (ABC) Project, a three-phase peer-led community program designed to promote cancer prevention by improving breast cancer screening rates among Chinese and Vietna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 25 publications
1
29
0
1
Order By: Relevance
“…Specifically, familiarity and comprehension subscales were considered particularly challenging with 54% and 36% of the study sample scoring zero on the subscales, respectively. Limited English proficiency was highly relevant to the high prevalence of low health literacy observed among recent immigrants in the U.S. (Berger et al, 2017;Jun & Nan, 2018;Sentell & Halpin, 2006). Indeed, despite a high level of education (about 65% having some college+ education) with an average length of stay in the U.S. being 16.5 years, only less than a quarter (23.4%) of the KA sample indicated their English as being fluent.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Specifically, familiarity and comprehension subscales were considered particularly challenging with 54% and 36% of the study sample scoring zero on the subscales, respectively. Limited English proficiency was highly relevant to the high prevalence of low health literacy observed among recent immigrants in the U.S. (Berger et al, 2017;Jun & Nan, 2018;Sentell & Halpin, 2006). Indeed, despite a high level of education (about 65% having some college+ education) with an average length of stay in the U.S. being 16.5 years, only less than a quarter (23.4%) of the KA sample indicated their English as being fluent.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have shown significant health literacy challenges in certain groups such as recent Asian immigrant in the U.S. who often lack English proficiency (Berger, Huang, & Rubin, 2017;Jun & Nan, 2018;Sentell & Halpin, 2006). KAs, one of the largest Asian populations in the U.S., are predominantly foreign born (92.5%) and monolingual (70% do not speak English well) (Shin, 2003).…”
mentioning
confidence: 99%
“…The need for well-controlled clinical studies is particularly important given the increasing incidence of breast cancer in Asian patients [6] and evidence that Asian patients may be more likely to die from breast cancer than other populations [7,13,14]. Evidence also suggests that patients are not treated according to international guidelines in some Asian populations [15,16], and there is a shortage of recommendations for use of G-CSF in Asian patients.…”
Section: Discussionmentioning
confidence: 99%
“…All but two of the patients in our study were based in India and Malaysia and as such represent two different patient populations, which in turn will differ to the Chinese and Japanese patients in the Zhang and Masuda studies. Evidence regarding breast cancer risk, prevalence and mortality from other continents suggests that Asian women in Western countries may be exposed to lifestyle factors that influence breast cancer incidence [18], and have differences in prevalence and mortality compared with other ethnic groups [7,13,14,19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Diante deste panorama é importante se realizarem ações de educação em saúde que possam estimular a participação da população por meio de rodas de conversas, palestras educativas e demonstrações práticas da autopalpação de mama. Isto se faz importante para que as mulheres possam ser sensibilizadas quanto a importância da adoção de hábitos saudáveis, como: praticar atividade física, alimentar-se de forma saudável, manter o peso corporal adequado, evitar o consumo de bebidas alcoólicas, amamentar, evitar uso de hormônios sintéticos -anticoncepcionais e terapias de reposição hormonal (9,16) .…”
Section: Figura 5: Demonstração Prática Da Autopalpação Da Mama Em Manequim Anatômicounclassified